PENGARUH KEWENANGAN SUPERVISOR TERHADAP RESPON AUDITOR DI LINGKUNGAN PERWAKILAN BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNANPROVINSI PAPUA (Studi Pada Instalasi Farmasi Kabupaten Dinas Kesehatan Kabupaten Pegunungan Bintang) - Susilo, Yustinus Tito; Asnawi, Meinarni; Wijaya, Anthonius H. C. (Fakultas Ekonomi, Universitas Cenderawasih, 2020)
The purpose of this study was to examine the effect of referent power variables, expert power,legitimate power, reward power, and coercive power as independent variables to performanceimprovement and impression management as dependent variables. This research has the purpose to answer the characteristic of exploratory, descriptive, explanation,and prediction research, using the survey method like questionnaire containing the question list thatwill be given to the respondent to be filled as purpose to get the information from the respondent.data processing using WarpPLS 5.0. The results of the study show that reference power, appreciation power, and coercive powerinfluence the improvement of performance and impression management, while expert power andlegitimate power have no effect on performance improvement and impression management.